Prevalence and risk factors for mild and high-frequency bilateral sensorineural hearing loss at age 11 years old: A UK prospective cohort study. - Hall, Amanda J.; Midgley, Elizabeth; Steer, Colin; Humphriss, Rachel (International Journal of Audiology, 2011)
Abstract Objective: This study aimed to assess prevalence and risk factors for mild/high-frequency bilateral sensorineural hearing loss within a UK population of children at age 11 years. Design: Prospective birth cohort study. Study sample: Repeat hearing thresholds were measured in 5032 children, as part of the Avon Longitudinal Study of Parents and Children (ALSPAC) at age 7, 9, and 11 years. Pregnancy, birth, and early medical history were obtained prospectively through parental questionnaires and medical records. Results: Twenty children had mild and seven had high-frequency bilateral sensorineural hearing loss, giving a combined prevalence of 0.5% (95% CI 0.4-0.8%). These children were more likely than the rest of the study sample to have been admitted to hospital at 6-18 months (OR 2.7, 95% CI 1.00-7.30). Parents of these children were more likely to have suspected a hearing problem when the children were 3 years old (OR 2.4, 95% CI 1.05-5.60). Conclusions: This is the first UK prospective cohort study to investigate the prevalence of mild and high-frequency hearing loss. This study, which has the advantage of a large sample size and repeat hearing measures over a four year period, reports lower prevalence values than US cross-sectional studies. Sumario Objetivo: Este estudio tiene como objetivo evaluar la prevalencia y los factores de riesgo para la hipoacusia bilateral sensorineural en frecuencias medias y altas dentro de la población de niños de 11 años de edad del Reino Unido. Diseño: Estudio prospectivo de cohorte desde el nacimiento. Muestra: Los umbrales auditivos de 2032 niños fueron medidos como parte del Estudio Longitudinal de Padres y Niños de Avon (ALSPAC) cuando los niños tenían 7, 9 y 11 años. La historia del embarazo, el nacimiento y de los primeros años se obtuvo en forma prospectiva mediante un cuestionario a los padres y por medio de archivos médicos. Resultados: Veinte niños tenían hipoacusia superficial y siete tenían hipoacusia sensorineural bilateral en frecuencias altas, lo que dio una prevalencia combinada del 0.5% [CI 0.4 - 0.8%]. Estos niños presentaban una mayor tendencia a haber sido internados en el hospital entre los 6 y los 18 meses [OR 2.7, 1.00 - 7.30]. Los padres de estos niños tuvieron una mayor tendencia a sospechar el problema auditivo cuando los niños tenían 3 años de edad [OR 2.4, 1.05 - 5.60]. Conclusiones: Este es el primer estudio prospectivo de cohorte que investiga la prevalencia de la hipoacusia superficial y en frecuencias altas. Este estudio, que tiene la ventaja de tener una muestra amplia y que repite las mediciones en un periodo de cuatro años, reporta unos valores de prevalencia menores que los estudios transversales en los EEUU.